2021
DOI: 10.1126/sciadv.abi5507
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin is a carbon dioxide–binding protein

Abstract: The identification of CO 2 -binding proteins is crucial to understanding CO 2 -regulated molecular processes. CO 2 can form a reversible posttranslational modification through carbamylation of neutral N-terminal -amino or lysine -amino groups. We have previously developed triethyloxonium (TEO) ion as a chemical proteomics tool for covalent trapping of carbamates, and here, we deploy TEO to identify ubiquitin as a mammalian CO 2 -binding protein. We use 13 C-NMR spectroscopy to demonstrate that CO 2 forms car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…TRAF2 is well known as an E3-ubiquitin ligase capable of facilitating K63 polyubiquitination, and also as a ubiquitin ligase important for NF-kappaB-dependent signaling cascades ( Zhou et al, 2013 ). These findings linking hypercapnia and an E3-ubiquitin ligase are of particular interest given the recent findings by the Cann group in Durham University implicating ubiquitin itself as a direct target for post-translational carboxylation ( Linthwaite et al, 2021 ).…”
Section: Original Research Papersmentioning
confidence: 87%
“…TRAF2 is well known as an E3-ubiquitin ligase capable of facilitating K63 polyubiquitination, and also as a ubiquitin ligase important for NF-kappaB-dependent signaling cascades ( Zhou et al, 2013 ). These findings linking hypercapnia and an E3-ubiquitin ligase are of particular interest given the recent findings by the Cann group in Durham University implicating ubiquitin itself as a direct target for post-translational carboxylation ( Linthwaite et al, 2021 ).…”
Section: Original Research Papersmentioning
confidence: 87%
“…When PreLysCar was applied to a subset of solved protein structures from the PDB (structures greater than 200 residues, solved by X-ray crystallography, containing 14,261 protein chains after 90% redundancy removal), it predicted that at least 1.3% of proteins with more than 200 amino acids in the PDB could potentially be subject to spontaneous lysine carboxylation. As the model has been trained using previously identified stable carbamates, which are predominantly buried, it may only represent a subset of possible KCX sites ( Linthwaite et al, 2020 ).…”
Section: Computational Approaches For the Identification Of Carbamate...mentioning
confidence: 99%
“… Linthwaite et al, 2021 recently explored the potential modification of human Ub by CO 2 . They demonstrated that Ub K33 and K48 could be carbamylated under physiological conditions by CO 2 (25 mM CO 2 /HCO 3 at pH 7.4), using the “trapping” method ( Figure 4 ) outlined in Linthwaite et al, 2018 .…”
Section: Mass Spectrometry Approaches For the Identification Of Carba...mentioning
confidence: 99%
See 2 more Smart Citations